Early Introduction of Subcutaneous Hepatitis B Immunoglobulin Following Liver Transplantation for Hepatitis B Virus Infection: A Prospective, Multicenter Study. Issue 7 (July 2016) - De Simone, Paolo; Romagnoli, Renato; Tandoi, Francesco; Carrai, Paola; Ercolani, Giorgio; Peri, Eugenia; Zamboni, Fausto; Mameli, Laura; Di Benedetto, Fabrizio; Cillo, Umberto; De Carlis, Luciano; Lauterio, Andrea; et al.
Abstract : Background: Subcutaneous administration of hepatitis B immunoglobulin (HBIg) is effective in preventing hepatitis B virus (HBV) recurrence after liver transplantation, but early conversion to subcutaneous administration is undocumented. Methods: In a prospective study, patients transplanted for terminal liver disease due to HBV infection who were HBV DNA-negative at transplant were switched by week 3 posttransplantation from intravenous to subcutaneous HBIg (500 or 1000 IU weekly or fortnightly, adjusted according to serum anti-HBs trough level) if they were HBsAg- and HBV-DNA negative at time of switch. All patients concomitantly received nucleos(t)ide analogue antiviral therapy. Primary endpoint was failure rate by month 6, defined as serum anti-HBs of 100 IU/L or less or HBV reinfection despite serum anti-HBs greater than 100 IU/L. Results: Of 49 patients treated, 47 (95.9%) continued treatment until month 6. All patients achieved administration by a caregiver or self-injection by week 14. No treatment failures occurred. Mean anti-HBs declined progressively to month 6, plateauing at a protective titer of approximately 290 IU/L. All patients tested for HBV DNA remained negative (45/45). Only 1 adverse event (mild injection site hematoma) was assessed as treatment-related. Conclusions: Introduction of subcutaneous HBIg administration by week 3 posttransplantation, combined with HBV virostatic prophylaxis, is effective and convenient for preventing HBV recurrence. Abstract : In this prospective multicenter study, HBV recurrence is effectively prevented in low-risk patients (HBV-DNA negative at transplant) after switching by week 3 posttransplant from intravenous to subcutaneous hepatitis B immunoglobulin with concomitant nucleos(t)ide analogue antiviral therapy.